2021
DOI: 10.1111/jcmm.16886
|View full text |Cite
|
Sign up to set email alerts
|

A novel naphthalimide derivative reduces platelet activation and thrombus formation via suppressing GPVI

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Nonetheless, it remains unclear whether the signaling cascades downstream of Akt directly participate in platelet activation, and further research is warranted to elucidate this aspect. Platelets express several downstream candidates of Akt, including GSK3 (α and β isoforms), with GSK3β being the most abundant protein [ 31 , 32 ]. Previous studies utilizing mice deficient in platelet-specific PI3Kβ have revealed the development of arterial thrombus instability, particularly under high shear stress conditions, due to impaired Akt/GSK3 activation within the growing thrombus [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it remains unclear whether the signaling cascades downstream of Akt directly participate in platelet activation, and further research is warranted to elucidate this aspect. Platelets express several downstream candidates of Akt, including GSK3 (α and β isoforms), with GSK3β being the most abundant protein [ 31 , 32 ]. Previous studies utilizing mice deficient in platelet-specific PI3Kβ have revealed the development of arterial thrombus instability, particularly under high shear stress conditions, due to impaired Akt/GSK3 activation within the growing thrombus [ 14 ].…”
Section: Discussionmentioning
confidence: 99%